Developing a Model of Human Management for Muslims in Creative Media Industries - Nur Kareelawati Abd. Karim; Rosidayu Sabran; Mohd Rosmizi Abd Rahman; Dini Farhana Baharudin; Muhammad Khairi Mahyuddin; Khatijah Othman; Eizan Azira Mat Sharif; Sami Salama Hussen Hajjaj (European Publisher, 2024)
Non-Indexed Publication